Frequency of isolated cutaneous involvement in adult mastocytosis: a cohort study. (17th May 2019) - Fradet, M.; Negretto, M.; Tournier, E.; Laurent, C.; Apoil, P.A.; Evrard, S.; Degboe, Y.; Del Mas, V.; Lamant, L.; Dubreuil, P.; Laroche, M.; Mailhol, C.; et al.
Abstract: Background: Mastocytosis is characterized by the accumulation/proliferation of abnormal mast cells. The frequency of isolated cutaneous involvement in adults with mastocytosis has not been fully determined. The main objective of our study was to assess the frequency of isolated cutaneous mastocytosis (CM) in adults with mastocytosis skin lesions. The second objective was to compare the clinical, histological, biological and imaging features in patients with isolated CM and patients with systemic mastocytosis (SM). Methods: We included all patients with histology‐proven mastocytosis skin lesions between January 2009 and December 2017. The mastocytosis diagnosis was made according to the international diagnostic criteria. All data were collected from a dedicated specific case report. Results: Among 160 patients with mastocytosis skin lesions, 25 patients had isolated CM (15.6%), 105 had SM and 30 (18.7%) patients had undetermined mastocytosis. Skin KIT mutation (OR: 51.9, 95% CI: 3.9–678, P = 0.001) and high bone marrow tryptase (OR: 97.4, 95% CI: 10.3–915, P = 0.001) were strong predictors of SM. The prevalence of osteoporosis was higher in the SM population than in the isolated CM population. Moreover, a decrease in bone mineral density over a short period of follow‐up (1–2 years) was associated with SM. There were no differences between the two groups regarding the frequency of mast cell activation symptoms, the presentation of skin lesions, the number of mast cells in the dermis and the level of serum tryptase. We propose considering the KIT mutation status and bone marrow tryptase levels to aid the diagnosis of isolated CM in adult mastocytosis patients. Conclusion: Only a small minority of adults with mastocytosis skin lesions has isolated cutaneous involvement. In 18.7% of mastocytosis cases, even complete workup does not allow for a precise classification of patients.